2018
DOI: 10.1001/jama.2018.2202
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Wisely Campaigns

Abstract: Choosing Wisely, a campaign to stimulate conversations between physicians and patients about unnecessary tests, treatments, and procedures, began in the United States in 2012. It was designed as a national campaign about overuse. Yet since its launch, the campaign has spread to more than 20 countries worldwide. Choosing Wisely has been hailed by some as a success, evident in its spread internationally and measured through structure and process indicators, such as recommendations developed, societies engaged, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 7 publications
1
95
0
2
Order By: Relevance
“…A key part of Choosing Wisely has been specialty societies putting together lists of recommendations to disseminate among their peers 5. Societies have autonomy to do this independently, resulting in considerable heterogeneity in scope.…”
Section: Supporting Doctors To Reduce Overusementioning
confidence: 99%
“…A key part of Choosing Wisely has been specialty societies putting together lists of recommendations to disseminate among their peers 5. Societies have autonomy to do this independently, resulting in considerable heterogeneity in scope.…”
Section: Supporting Doctors To Reduce Overusementioning
confidence: 99%
“…The approach of clinician leadership and professionalism as a means to address the problem of overuse has resonated. It is suggested that the campaign has spread widely because of (a) the perceptions of the campaign as an innovation within medicine; (b) the role of physician leadership as key component of campaigns; and (c) the context of campaigns bringing together diverse stakeholders committed to a common problem …”
Section: Choosing Wisely Around the Worldmentioning
confidence: 99%
“…Similar efforts have been planned or launched in Germany, Austria, Australia, New Zealand, England, Wales, Italy, Netherlands, Norway, Portugal, France, Israel, Brazil and Japan with other countries planning or in early stages of launching national campaigns. Internationally, CW leaders from existing or planned national CW campaigns meet yearly to discuss implementation of the recommendations in their respective countries and collectively have formed a collaborative learning community 13…”
Section: Introductionmentioning
confidence: 99%